2023
DOI: 10.1161/circimaging.122.015120
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Incremental Prognostic Value of Pericoronary Adipose Tissue Computed Tomography Attenuation Beyond Coronary Artery Disease Reporting and Data System for Major Adverse Cardiovascular Events in Patients With Acute Chest Pain

Abstract: Background: Pericoronary adipose tissue (PCAT) and Coronary Artery Disease Reporting and Data System (CAD-RADS) category had prognostic values for major adverse cardiovascular events (MACEs). However, little is known about the difference between CAD-RADS and PCAT computed tomography (CT) attenuation for predicting MACEs. This study was to compare the prognostic value of PCAT and CAD-RADS for MACEs in patients with acute chest pain. Methods: Between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The contribution of EAT to the progression of coronary atherosclerosis is well recognized [43,44]. However, the usefulness of EAT attenuation for risk stratification and prediction of major acute cardiac events remains controversial in patients with CAD [45][46][47].…”
Section: Epicardial Adipose Tissuementioning
confidence: 99%
“…The contribution of EAT to the progression of coronary atherosclerosis is well recognized [43,44]. However, the usefulness of EAT attenuation for risk stratification and prediction of major acute cardiac events remains controversial in patients with CAD [45][46][47].…”
Section: Epicardial Adipose Tissuementioning
confidence: 99%
“…In contrast, recent studies have shown that the pericoronary adipose tissue (PCAT) can be used as a marker of coronary artery inflammation [ 12 , 13 ]. and is closely associated with a variety of cardiovascular diseases [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it independently predicts long-term MACEs (Major Adverse Cardiac Events) in patients with acute myocardial infarction. 25 , 26 Nevertheless, previous research has not examined the relationship between adipose tissue volume and FAI around the left anterior descending artery (LAD) and the circumflex artery (LCX) in relation to acute myocardial infarction, nor has it analyzed the adipose tissue surrounding non-culprit lesion vessels during acute myocardial infarction. As a result, it remains unclear whether plaque rupture triggered by vascular inflammation during acute myocardial infarction solely induces inflammation in the corresponding culprit coronary artery adipose tissue, or if it also provokes inflammation in the entire epicardial vascular adipose tissue.…”
Section: Introductionmentioning
confidence: 99%